The Effect of NPF, FDR, Bank Size and Covid-19 on MSME Financing of Indonesian Sharia Commercial Banks for the 2018-2021 Period - Fitri Anisa Nusa Putri; Muhammad Wakhid Musthofa (Al Iqtishod: Jurnal Pemikiran dan Penelitian Ekonomi Islam, 2023)
MSME has a massive contribution to national economic development. In order to expand and strengthen the MSME sector, Islamic Commercial Banks as financial intermediary should consider some of the main factors before distributing their financing to the MSME sector. This study aims to identify and analyze the effect of NPF, FDR, Bank Size, and Covid-19 on MSME Financing at Shariah Rural Banks in Indonesia in the period of 2018-2021 both partially and simultaneously. This study uses a panel data approach where the data needed in this study are from 7 Indonesian Islamic Banks with 112 of total data quarterly. The data was collected from quarterly Islamic bank reports. The results of this study indicate that FDR and Bank Size variables have a positive significant effect on MSMEs Financing at Shariah Rural Banks. Meanwhile, NPF and the dummy variable Covid-19 have no significant effect on MSMEs Financing at Shariah Rural Banks. This study is expected to developing of the grand theory and knowledge on the impact of MSME Financing especially in the Shariah Rural Banks in Indonesia.